The Broken Body in a Broken World: A Contribution to a Christian Doctrine of the Person from a Disabled Point of View - Hull, John M. (Journal of religion, disability & health, 2004)
There are considerable advantages for a Christian theology of disability when the Christian doctrine of the person takes as its starting point not the image of God, but the broken body of Christ. This starting point leads us away from aspects of Christian tradition which tend to marginalise disabled people toward those which emphasise disability as an alternative theology to the theology of perfection and power. The implications of such a theology of brokenness are illustrated from the New Testament and the subsequent development of the doctrine of the Heavenly Session. The article concludes by suggesting a distinctive ministry of disabled people.